Fish oil replacement in finfish nutrition - Giovanni Turchini; B Tortensen; W K Ng (2009)
Unsustainable fishing practices have placed a heavy emphasis on aquaculture to meet the global shortfalls in the supply of fish and seafood, which are commonly accepted as the primary source of health-promoting essential omega-3 (n-3 highly unsaturated fatty acids). However, dietary fish oil is required for the production of omega-3-rich farmed fish and this commodity, in a vicious circle, is at present derived solely from wild fisheries. Decreasing global availability coupled with the highly variable price of this resource has forced the aquaculture industry to investigate the possibilities of alternative dietary lipid sources. This review attempts to compile all principal information available regarding the effects of fish oil replacement for the diets of farmed finfish, analysing the findings using a comparative approach among different cultured fish species. The review initially focuses on the present situation with regard to the production, availability and main nutritional characteristics of fish oil and the principal alternative lipid sources (such as vegetable oils and animal fats). Following this, the effects of fish oil replacement in finfish nutrition on feed quality, fish performance, feed efficiency, fish lipid metabolism, final eating quality and related economic aspects are presented and discussed.